Kafka's Nonhuman Form Troubling the Boundaries of the Kafkaesque - Geier, Ted.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book is a compact study of Kafka's inimitable literary style, animals, and ecological thought-his nonhuman form-that proceeds through original close readings of Kafka's oeuvre. With select engagements of Adorno, Derrida, and the literary heritage from Romanticism to Dickens that influenced Kafka, Ted Geier discusses Kafka's literary, "nonhuman" form and the way it unsettles the notion of a natural and simple existence that society and culture impose, including the boundaries between human and animal. Through careful attention to the formal predicaments of Kafka's works and engaging with Kafka's original legal and social thought in his novels and short stories, this book renders Kafka's sometimes impossibly enigmatic work legible at the level of its expression, bringing surprising shape to his work and redefining what scholars and readers have understood as the "Kafkaesque". Ted Geier is currently Andrew W. Mellon Postdoctoral Fellow at Rice University and the founder of the Interdisciplinary Animal Studies Group at the University of California, Davis, USA. He has taught comparative literature, cinema, Romanticism, and American cultural studies at San Francisco State University, Davis, and Rice. He is the author of articles and book chapters on animals and ecology in the works of Italo Calvino, recent world literature, and British literature of the long nineteenth century, in addition to ecocinema, especially in the work of Terrence Malick. .
Introduction: Present progression, always-already: grammars of the nonhuman -- Chapter One: Digging in (not digging it): obsessive creatures and sociality -- Chapter Two: Finding oneself awoken from: nonhuman metamorphoses -- Chapter Three: Unlike a dog, having done nothing wrong: after the law -- Conclusion: Interminable subjects -- Works Cited or Consulted -- Index.
Keywords: European literature; Literature-Philosophy.; Literature, Modern-20th century